The configuration of biology teaching: a concern for pedagogy - Roa, Paola Andrea (Universidad Pedagógica y Tecnológica de Colombia, 2020)
Some problematic nodes in the configuration of biology teaching are presented, which allow us to question the place of pedagogy in its journey through the history of theColombian school, in order to contribute to the current constitution of its subject of matter. A genealogical look at the archive—1890-2016—allows us to state that biology emerged in the Colombian school in the first half of the last century due to conditions related to education and socio-cultural purposes. Its teaching has been linked to doing science in school and has been related to the natural sciences—in terms of the notions of integration and interdisciplinarity—and currently to its displacement about environmental education and interculturality. These are proposed as nodes that point to the absence of pedagogy in its configuration or its reduction to the sciences of education, to the attempt to reproduce biological science and to didactics—understood as the ways of doing science in school.